Anterior cleft palate due to Cbfb deficiency and its rescue by folic acid - Safiye E. Sarper; Toshihiro Inubushi; Hiroshi Kurosaka; Hitomi Ono Minagi; Yuka Murata; Koh-ichi Kuremoto; Takayoshi Sakai; Ichiro Taniuchi; Takashi Yamashiro (The Company of Biologists, 2019)
Core binding factor β (Cbfb) is a cofactor of the Runx family of transcription factors. Among these transcription factors, Runx1 is a prerequisite for anterior-specific palatal fusion. It was previously unclear, however, whether Cbfb served as a modulator or as an obligatory factor in the Runx signaling process that regulates palatogenesis. Here, we report that Cbfb is essential and indispensable in mouse anterior palatogenesis. Palatal fusion in Cbfb mutants is disrupted owing to failed disintegration of the fusing epithelium specifically at the anterior portion, as observed in Runx1 mutants. In these mutants, expression of TGFB3 is disrupted in the area of failed palatal fusion, in which phosphorylation of Stat3 is also affected. TGFB3 protein has been shown to rescue palatal fusion in vitro. TGFB3 also activated Stat3 phosphorylation. Strikingly, the anterior cleft palate in Cbfb mutants is further rescued by pharmaceutical application of folic acid, which activates suppressed Stat3 phosphorylation and Tgfb3 expression in vitro. With these findings, we provide the first evidence that Cbfb is a prerequisite for anterior palatogenesis and acts as an obligatory cofactor in the Runx1/Cbfb-Stat3-Tgfb3 signaling axis. Furthermore, the rescue of the mutant cleft palate using folic acid might highlight potential therapeutic targets aimed at Stat3 modification for the prevention and pharmaceutical intervention of cleft palate.